Pengaruh Wirid Yasin terhadap Spiritualitas Kaum Ibu di Kecamatan Sawang - Nazari Mahda; Fuad Ramly; Raina Wildan (Program Studi Aqidah dan Filsafat Islam, 2021)
The article is based on a research report (field research) which aims to examine the understanding, efforts and influence of wirid yasin practice on women's spiritual awareness in Sawang District, South Aceh Regency. This study uses a qualitative approach, data collected through documentation, observation, and interviews. Data analysis was carried out descriptively and supported by interpretation and triangulation of data. This study concludes that women in Sawang Subdistrict recognize wirid yasin as a tradition to improve the quality of their faith, religious knowledge, brotherhood and blessings. The revitalization of wirid yasin is carried out not only by establishing educational programs and teaching religious knowledge, but also by improving the quality of wirid yasin practice. This practice has succeeded in increasing spiritual awareness among women, in terms of increasing their piety, obedience to worship, muraqabah and gratitude to Allah in living their daily lives.